Extent of Adopting New Public Management Strategies in The Nigerian Public Service - Alamu, Oluwaseyi Isaiah; Makinde, Wasiu Abiodun; Shiyanbade, Bolanle W. (UI Scholars Hub, 2026)
The Nigerian public service has faced significant challenges in delivering quality services to citizens, which necessitate the adoption of New Public Management (NPM) strategies. New Public Management focused on improving the quality-of-service delivery and public sector performance through a market-oriented approach of performance measurement, decentralization of decision making, performance contracting, and accountability for results, among others. This study examines the extent of adoption of NPM strategies in the Nigerian public service using the selected federal ministries of Nigeria. Survey research design through qualitative and quantitative (mixed method) approaches was used for data collection and analysis. The population of the study comprised 5,150 senior staff from Grade Level 7 and above at the headquarters of the Federal Ministries of Nigeria as of 31st August, 2024. The study adopted a multi-stage sampling technique. Krejcie and Morgan's sampling technique was applied to the population to have a sample size of 357 for questionnaire administration. Quantitative data collected through questionnaire administration were analyzed using descriptive statistics of the frequency distribution table and inferential statistics of Analysis of Variance (ANOVA). Qualitative data collected through semi-structured interview sessions with sampled respondents were analyzed using thematic analysis. The study revealed from the result of the analysis of variance that there are differences in the extent of adopting accountability for results (F4,313=14.457, p<0.005), decentralization of decision-making (F4,313=14.092, p<0.005), performance measurement (F4,313=51.187, p<0.005), performance contracting (F4,313=9.444, p<0.005), and use of information technology (F4,313=11.567, p<0.005) in the selected Federal Ministries of Nigeria. The study concluded that there are differences in the adoption of NPM strategies in the Nigerian public service, influencing the quality of service delivery and public sector performance.